Productivity and technological quality of sugarcane cultivars fertigated and planted through pre-sprouted seedlings - Coelho, Anderson Prates [UNESP]; Dalri, Alexandre Barcellos [UNESP]; de Faria, Rogério Teixeira [UNESP]; Landell, Estêvão Pacheco de Andrade [UNESP]; Palaretti, Luiz Fabiano [UNESP]; Zanini, José Renato [UNESP]; Zerbato, Cristiano [UNESP] (Southern Cross Publishing, 2018)
The increase in sugarcane production in Brazil does not only depend on the increase of cultivated areas. It also needs alternatives to increase productivity. These alternatives include irrigation, planting method, and development of new cultivars. In this scenario, the use of pre-sprouted seedlings is particularly relevant because it ensures high phytosanitary standards and uniform crops. The objective of this work was to evaluate the productivity and technological characteristics of five sugarcane cultivars that were planted through pre-sprouted seedlings and conducted with and without supplementary irrigation in the second growing year. The experiment was conducted at the FCAV/UNESP, in Jaboticabal, São Paulo state, Brazil, from 2015 to 2016. The treatments were distributed in a partially balanced incomplete block design, with three cultivars per block. Supplementary irrigation was performed when there was an accumulated water deficit of 30 mm. Reference evapotranspiration was calculated according to the FAO-56 method. The evaluated sugarcane cultivars were: CTC 4, IACSP 93-3046, RB 86-7515, IACSP 95-5000, and IAC 91-1099. The total irrigation depth applied during the cycle was 360 mm. Supplementary irrigation triggered a decrease in the sugarcane technological indices, mainly for the cultivars CTC 4 and IAC 91-1099, presenting a 15% apparent sucrose (POL%) cane reduction in the non-irrigated treatment, and 14% in the irrigated. Cultivar IAC 91-1099 stood out in the productivity of sugar and stalks, with productivities of 24.16 t ha-1 of sugar and 166 t ha-1 of stalk under irrigation using pre-sprouted seedlings.
Keywords: Cultivar; Evapotranspiration; Irrigation; Saccharum spp.; Water management